Analisis Efektivitas Oil Cooler Generator Thrust Bearing Pada Unit 2 di PLTM Parmonangan - Siagian, Steven Owen Yosua; Winaya, I N. Suprapta; Tenaya, I G.N. Putu (Teknik Desain Mekanika, 2021)
Abstract To maintain the reliability of the Parmonangan PLTM production, you must use auxiliary equipment that can work optimally, including the Oil Cooler Generator Thrust Bearing. This study aims to analyze the actual heat transfer rate, NTU and the effectiveness of the oil cooler generator thrust bearing after maintenance 1 and maintenance 2. After maintenance 1, the effectiveness value decreased over time from 40.29% to 27.03%. After maintenance, theaeffectiveness of thecoil cooler increasedwagain froma27.03% to 40.27%. On day 1 to day 13 the effectiveness value is the same, after from day 13 to day 17 the effectiveness value begins to decrease. Even the effectiveness value after maintenance 2 is lower than after maintenance 1 due to the running time of operation. Therefore, regular maintenance scheduling is carried out in order to always maintain good conditions of effectiveness. Keywords: Oil Cooler, effectiveness, Maintenance, NTU